Opredelenie effektivnoj struktury podgotovki junych sportsmenov 12-13 let, specializirujušcichsja v karate - Korzhenevskiy, A. N.; Podlivaev, B. A.; Zhukov, S. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2021)
The work determined the effectiveness of the developed standards and model characteristics of technical, physical and functional readiness for young karateka 12-13 years old. Revealing the strengths and weaknesses of preparedness made it possible to develop an optimal structure of training for young athletes, which, in contrast to the generally accepted one, is characterized by an increase in the intensity of the exercises performed and an increase in the volume of special-oriented loads.